CORRELATION OF INTERLEUKIN-23 SERUM LEVELS IN MEN WITH ACNE VULGARIS: A PRELIMINARY STUDY - Maria Hotmaida Carolina Munthe; Novi Kusumaningrum; Amallia Nuggetsiana Setyawati; Astika Widy Utomo; Santoso Santoso (Jurnal Kedokteran Diponegoro, 2021)
Background: Acne vulgaris (AV) is an inflammatory condition of pilosebaceous unit that is common in adolescents and young adults. The pathogenesis of AV is multifactorial, one of which is inflammation. Interleukin-23 (IL-23) has an important role in the activity of T helper 17 (Th17) cells that produce IL-17 in chronic inflammation.